The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.neuropsychologia.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

The role of hearing ability and speech distortion in the facilitation of articulatory motor cortex

Abstract: Excitability of articulatory motor cortex is facilitated when listening to speech in challenging conditions. Beyond this, however, we have little knowledge of what listener-specific and speech-specific factors engage articulatory facilitation during speech perception. For example, it is unknown whether speech motor activity is independent or dependent on the form of distortion in the speech signal. It is also unknown if speech motor facilitation is moderated by hearing ability. We investigated these questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 54 publications
6
29
2
Order By: Relevance
“…This is in keeping with previous reports of behavioural changes post-TMS, which predominantly manifest in a change in response time (Devlin, Matthews, & Rushworth, 2003;Krieger-Redwood, Gaskell, Lindsay, & Jefferies, 2013;Pobric, Jefferies, & Ralph, 2007;Whitney, Kirk, O'Sullivan, Lambon Ralph, & Jefferies, 2011). Surprisingly, MEPs were not modulated by distorted sentences, despite this form of distortion modulating MEPs to pre-lexical stimuli (Nuttall, Kennedy-Higgins, Devlin, & Adank, 2017;Nuttall et al, 2016). MEPs were not affected by cTBS when considered at group level.…”
Section: Discussionsupporting
confidence: 91%
“…This is in keeping with previous reports of behavioural changes post-TMS, which predominantly manifest in a change in response time (Devlin, Matthews, & Rushworth, 2003;Krieger-Redwood, Gaskell, Lindsay, & Jefferies, 2013;Pobric, Jefferies, & Ralph, 2007;Whitney, Kirk, O'Sullivan, Lambon Ralph, & Jefferies, 2011). Surprisingly, MEPs were not modulated by distorted sentences, despite this form of distortion modulating MEPs to pre-lexical stimuli (Nuttall, Kennedy-Higgins, Devlin, & Adank, 2017;Nuttall et al, 2016). MEPs were not affected by cTBS when considered at group level.…”
Section: Discussionsupporting
confidence: 91%
“…Based on research into the relationship between action and language, the view that both phonetic and semantic processing shares cognitive and neural resources with the sensorimotor system has gained increasing acceptance (Barsalou, ; Fischer & Zwaan, ; Willems & Hagoort, ). For example, comprehending the meanings of words semantically related to body parts (e.g., eat , mouth ) activates brain regions also engaged in moving these body parts(Andrews, Frank, & Vigliocco, ; Meteyard, Cuadrado, Bahrami, & Vigliocco, ; Pulvermüller, ), just like decoding sounds recruits regions responsible for the production of these sounds (Nuttall, Kennedy‐Higgins, Devlin, & Adank, ; Skipper, Devlin, & Lametti, ).…”
Section: Hierarchical Structure In Language and Actionmentioning
confidence: 99%
“…Changes in the size of MEPs reflect changes in the excitability of the motor pathways connecting the cortical representations with the corresponding muscles. Using this technique, several studies have demonstrated that the excitability of the primary motor cortex, which controls articulatory gestures to produce speech, is enhanced during listening to speech ( Fadiga et al., 2002 , Murakami et al., 2011 , Murakami et al., 2013 , Nuttall et al., 2017 , Nuttall et al., 2016 , Watkins et al., 2003 ).…”
Section: Introductionmentioning
confidence: 99%